Working PeopleSmart : 6 strategies for success - Silberman, Melvin L.; Hansburg, Freda, 1950- (San Francisco : Berrett-Koehler, 2004)
Bringing out the best in others is good business. When we bring both respect and interpersonal savvy to our work relationships, we do more than make people feel good. We enhance personal and organizational performance. And as the workplace grows more complex and competitive, managing our work relationships becomes even more essential and difficult. Now more than ever we need to work people smart. Working PeopleSmart describes the six core strategies used by people-smart individuals and shows how to apply them in the toughest workplace situations. Individuals who are people smart know how to op.
Preface; Introduction; Strategy 1: Be Curious Rather than Furious; Strategy 2: Include the Listener Rather than Talk at Him or Her; Strategy 3: Speak Up (with Tact) Rather than Suffer in Silence; Strategy 4: Invite Others to Be Your Mirror Rather than Your Blind Spot; Strategy 5: Be Open to Resistance Rather than Fight It; Strategy 6: Think We, Not Me; Now What?; Index; About the Authors; PeopleSmart Products and Services.
Includes index.
English.
eBooks on EBSCOhost
Keywords: Psychology, Industrial -- Handbooks, manuals, etc; Success in business -- Handbooks, manuals, etc; Interpersonal relations -- Handbooks, manuals, etc; Organizational effectiveness -- Handbooks, manuals, etc; Psychologie du travail -- Guides, manuels, etc; Succès dans les affaires -- Guides, manuels, etc; Efficacité organisationnelle -- Guides, manuels, etc; BUSINESS & ECONOMICS -- Mentoring & Coaching; BUSINESS & ECONOMICS -- Motivational; Interpersonal relations; Organizational effectiveness; Psychology, Industrial; Success in business; Interpersoonlijke relaties; Arbeids- en organisatiepsychologie; Sociale beïnvloeding.; Organisatiegedrag; handbooks; Handbooks and manuals; Handbooks and manuals; Guides et manuels